Micromagnetic simulation of Nd–Fe–B grain with a dysprosium-containing shell - Kai Li; Yingying Dai; Zhiming Dai; Zhenhua Wang; Da Li; Wei Liu; Zhidong Zhang (AIP Advances)
The effects of Dy-doped shell thickness on the magnetic properties and magnetization reversal behavior of a Nd–Fe–B grain have been systematically investigated using micromagnetic simulations based on a core–shell model. The Dy-containing shell can significantly enhance the coercivity of the model. Notably, when the shell thickness reaches 12 nm, the coercivity reaches its maximum value, and the nucleation sites shift from the core–shell interface to the grain corners. Ferromagnetic resonance spectra indicate that the low-frequency modes are associated with the nucleation sites, and the increased coercivity is related to the shift of the core–shell simultaneous resonance mode to higher frequency. In addition, we propose a multi-shell model to further enhance the coercivity by shifting the nucleation points. This approach of adjusting the nucleation sites can also be applied to improve the magnetic properties of other magnets.